NURTURING STUDENTS' WRITING NARRATIVE INTEREST THROUGH MIND MAPPING AND COOPERATIVE INTEGRATED READING AND WRITING - Ratih Inayah; Ningtyas Orilina Argawati (Indonesian EFL Journal, 2019)
This study aims to investigate the motivation of senior high school students at 11st grade in reading and writing English texts, especially narrative text. The study also explores the insight toward the use of mind mapping and cooperative integrated reading and writing in nurturing students’ interest and motivation in writing narrative text. The study used qualitative case study to learn and pay attention to phenomena that the students’ motivation in reading and writing narrative text are needed to be nurtured. There were 36 students of 11st grade in senior high school in Bandung were involved in this study. Questionnaire and interview were given to the students. The results show that the students who show positive view toward reading and writing narrative texts are 74% students. They interest and willingness in making mind mapping of the narrative, because they know that narratives texts are full of information and moral value. While only 26% students who seem force to read and write narratives text to compose mind mapping. Eventually, integrating reading and composition in the classroom can nurture their reading interest and increase their willingness to read narrative text. Since, many students can understand the moral value of the narrative text through discussing with their friends at the class and making a mind mapping through cooperative learning about the narrative text is very useful to develop their mind.